1992
DOI: 10.1093/protein/5.4.351
|View full text |Cite
|
Sign up to set email alerts
|

Interchain cysteine bridges control entry of progesterone to the central cavity of the uteroglobin dimer

Abstract: The progesterone-binding protein uteroglobin has been expressed in Escherichia coli in an unfused, soluble form. Like mature uteroglobin from rabbit endometrium (UG), the E.coli produced uteroglobin (UG1) dimerizes in vitro, forms an antiparallel dimer with Cys3-Cys69' and Cys69-Cys3' disulfide bonds and binds progesterone under reducing conditions. In order to analyze the dimerization and the reduction dependence of progesterone binding in more detail, we separately replaced cysteine 3 and cysteine 69 by seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The expression plasmid pT7-UG1 [33] was used as a template to amplify the entire coding sequence of mature rab-UG by the PCR. The oligonucleotides were designed with NcoI and XhoI restriction endonuclease sites at the initiation and termination codons, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The expression plasmid pT7-UG1 [33] was used as a template to amplify the entire coding sequence of mature rab-UG by the PCR. The oligonucleotides were designed with NcoI and XhoI restriction endonuclease sites at the initiation and termination codons, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that recombinant rabbit and hUGs , Mantile et al, 1993 are virtually identical both structurally Morize et al, 1987) and functionally Mantile et al, 1993). The many and varied biological properties of UG and hUG described so far are suggested to be related to either their PLA2-inhibitory property (Levin et al, 1986;Miele et al, 1988;Singh et al, 1988a,b;Miele et al, 1990;Facchiano et al, 1991;Mantile et al, 1993) or due to their ability to bind various xenobiotic agents (Beato, 1976(Beato, , 1977Fridlansky and Milgrom, 1976;Atger et al, 1980;Bochskenal and Kirchner, 1981;Gillener, 1988;Nordlund-Moller er al, 1990;Peter et al, 1992; Lopez de Haro and Neato, 1994). However, some of the biological properties of UG, such as its ability to inhibit chemotaxis, phagocytosis, thrombin-induced platelet aggregation, and cell proliferation may not be explainable on the basis of the known physicochemical properties of this protein.…”
Section: Profile Of Patients With Atopic Asthma Andmentioning
confidence: 99%
“…This protein possesses varied biochemical and biological properties including phospholipase A2(PLAA)-inhibitory (Levin et al, 1986), immunomodulatory (Mukherjee et al, 1982(Mukherjee et al, , 1983)/antiinflammatory properties (Levin et al, 1984;Miele et al, 1988;Mukherjee et al, 1988;Camussi et al, 1990a,b,c;Chan et al, 1990Chan et al, , 1991Di Rosa and Ialenti, 1990;Ialenti et al, 1990;Facchiano et al, 199l;Tetta etal, 1991;Perretti etal, 1991;Cabre' et al, 1992;Moreno et al, 1995). It binds xenobiotic agents such as progesterone (Beato, 1976(Beato, , 1977Fridlansky and Milgrom, 1976;Alger etal., 1980;Bochskanl and Kirchner, 1981;Peter, 1992), polychlorinated biphenyls (Gillener et al, 1988;NordlundMoller et al, 1990), and retinol (Lopez de Haro et al, 1994). Because of its potent PLA2-inhibitory, immunomodulatory/antiinflammatory activities and its high level of constitutive expression in the pulmonary system, it has been suggested that this protein may play critical roles in controlling inflammation in the airway (Mukberjee etal., 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Ac-TPSSYETSKEF-NH z (UTG [17][18][19][20][21][22][23][24][25][26][27][28] deprotected by thiolysis (PhSH/DIEA/DMF; 3:3:4, 50 equiv) before peptide cleavage when Dnp was used [26]. Acidolytic cleavages were performed with anhydrous liquid HF containing 10% anisole at 0 °C, except for UTG(48-70), which was cleaved from the resin using low-high HF conditions in order to reduce methionine sulfoxide in situ.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…1; the picture was generated with MOL-SCRIPT [13]). The progesterone-protein complex has never been isolated, but experiments carried out in vitro with the protein and some analogues have shown that Tyr 2', Thr 6° [14] and His 8 [15][16][17] are crucial for binding and that disulfide bridges play an essential role, controlling the entrance of the steroid to the channel through which the hydrophobic cavity can be reached [18]. The particular tertiary structure of uteroglobin and the fact that the mechanism of complexation remains unsolved moved us to start studying this protein.…”
Section: Introductionmentioning
confidence: 99%